2015
DOI: 10.1016/j.jbusres.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce technology adoption: A Malaysian grocery SME retail sector study

Abstract: This is the Accepted Manuscript version of the following article: S. Kurnia, et al., ???E-commerce technology adoption: A Malaysian grocery SME retail sector study???, Journal of Business Research, Vol. 68(9): 1906-1918, March 2015. The final published version is available at: https://doi.org/10.1016/j.neo.2016.09.002 Copyright ?? 2016, Elsevier.Electronic commerce (EC) has substantial potential to foster the growth of small and medium-sized enterprises (SMEs) in developed and developing countries alike. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
149
0
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(220 citation statements)
references
References 78 publications
11
149
0
23
Order By: Relevance
“…E-commerce becomes important thing for transaction in life in 21st century (Kurnia et al, 2015). Various services in E-commerce have developed in the last few years and consumers have adopted the services as parts of their everyday life and therefore, many people use E-commerce (Sharma & Lijuan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…E-commerce becomes important thing for transaction in life in 21st century (Kurnia et al, 2015). Various services in E-commerce have developed in the last few years and consumers have adopted the services as parts of their everyday life and therefore, many people use E-commerce (Sharma & Lijuan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it saves time, money and labor [3] of the consumers. Several studies on the usage of online shopping identified different factors, such as demographic factors, behavioral factors, infrastructural factors and so on [4]- [6]. Different studies identified the barriers of online shopping expansion globally [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…At last, the author pointed out that Chinese cross-border e-commerce would be greater development after the reform and innovation of the leading policy [9]. In addition, there are many scholars having conducted a study of electronic commerce [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%